2005
DOI: 10.1074/jbc.m504256200
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Lipid Rafts Inhibits P2X1 Receptor-mediated Currents and Arterial Vasoconstriction

Abstract: P2X 1 receptors for ATP are ligand-gated cation channels expressed on a range of smooth muscle preparations and blood platelets. The receptors appear to be clustered close to sympathetic nerve varicosities and mediate the underlying membrane potential changes and constriction following nerve stimulation in a range of arteries and resistance arterioles. In this study we have used discontinuous sucrose density gradients, Western blot analysis, and cholesterol measurements to show that recombinant and smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 57 publications
5
75
0
1
Order By: Relevance
“…P2X 1 receptor knockout mice have confirmed, in mesenteric arteries, the involvement of P2X 1 receptors in ATP-mediated vasoconstriction and transient inward currents and in sympathetic neurogenic vasoconstriction (Vial and Evans, 2002). Moreover, P2X 1 receptor clusters have been described on vascular smooth muscle in regions adjacent to sympathetic nerve varicosities (Hansen et al, 1999;Vial and Evans, 2005) and provide an explanation for why smooth muscle P2X receptors, and not P2Y receptors, are involved in ATP cotransmission.…”
Section: Dual Control Of Vascular Tone By Perivascular Nerves Andmentioning
confidence: 85%
“…P2X 1 receptor knockout mice have confirmed, in mesenteric arteries, the involvement of P2X 1 receptors in ATP-mediated vasoconstriction and transient inward currents and in sympathetic neurogenic vasoconstriction (Vial and Evans, 2002). Moreover, P2X 1 receptor clusters have been described on vascular smooth muscle in regions adjacent to sympathetic nerve varicosities (Hansen et al, 1999;Vial and Evans, 2005) and provide an explanation for why smooth muscle P2X receptors, and not P2Y receptors, are involved in ATP cotransmission.…”
Section: Dual Control Of Vascular Tone By Perivascular Nerves Andmentioning
confidence: 85%
“…The discrepancy between the latter results on the one hand and the results of Bannas et al (32) and our own data on the other hand might be explained by differences in cell types or in the procedures used in the preparation of rafts. More recently, Vial and Evans (34) reported that P2X 1 receptors colocalize with raft markers in arterial smooth muscle. Disruption of rafts with MCD blocked purinergicmediated currents and smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the regulatory role of flotillin-1 in IGF-1R signaling, independently of caveolin-1, caveolin-2 and caveolae, HEK293T cells that expressed no caveolins Torres et al, 2006;Vial and Evans, 2005) were stably transfected with shorthairpin RNA (shRNA) against flotillin-1 and tested for IGF-1-induced signaling activation (Fig. 1).…”
Section: Loss Of Flotillin-1 Leads To Inhibition Of Igf-1r Signaling mentioning
confidence: 99%